STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT KECAMATAN TANAH ABANG KABUPATEN PENUKAL ABAB LEMATANG ILIR - Puspa Utami; desti pratiwi (Program Studi Perbankan Syariah, 2024)
This research aims to find out how to analyze Human Resource Management Strategies in Improving Employee Performance at the Tanah Abang District Office, PALI Regency. The Tanah Abang District Head Office, Penukal Abab Lematang Ilir Regency is one of the government agencies in Penukal Abab Lematang Ilir Regency and has the aim of serving the community. This research uses descriptive qualitative research methods, by collecting data obtained through interviews, observation and documentation. Apart from that, the validity of the data was tested using triangulation. The informants in this research were the sub-district head, the head of the division. Community and Village Empowerment Sector, Finance Staff, Trantib Staff, Government and Community Heads. The results of this research found that the strategies implemented in HR management at the Tanah Abang District Office, PALI Regency have been working well. There are several alternatives that can be implemented, including making good plans, organizing human resources in determining job desks that are in accordance with the skills they have, providing routine direction, intensive control, and providing facilities to improve the quality of human resources, such as training to improve employee skills. . This is based on 10 aspects that serve as benchmarks for increasing employee performance, such as abilities and skills, knowledge, work design, personality, work motivation, leadership, leadership style, organizational culture, job satisfaction and work environment.